Systemic Inflammatory Response during Laparotomy - Ahmad Mahamid; Basel Jabarin; Gidon Almogy (Hindawi Limited, 2014)
Background. The aim of this study was to analyze the influence of laparotomy on the systemic inflammatory response in human patients suffering from secondary peritonitis. Study Design. A prospective study investigating the levels of white blood cells, C-reactive protein, platelets, interleukin-six, and tumor necrosis factor-alpha during laparotomy in five patients who suffered from secondary peritonitis. Six venous blood samples were collected perioperatively from each patient. The data were summarized by descriptive statistics and presented in a box plot. The hypothesis was that laparotomy increases the systemic inflammatory response, as has been described in animal models in previous studies. Results. The median age of the patients in this study was 84 years, the male to female ratio was 2 : 3, and the mortality rate was 80%. The most common cause of generalized peritonitis was ischemia of the colon. Analysis of the data showed no significant changes in the level of plasma inflammatory mediators during the surgical procedure, except for the platelet count which showed a significant decrease (P=0.001). Conclusions. In contrast to experience with animal models, laparotomy in human patients with secondary peritonitis did not significantly increase the systemic inflammatory response. Furthermore, it contributed in significantly decreasing some of the systemic inflammatory mediators.